2020
DOI: 10.1161/circresaha.119.316007
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin-TFEB-p62 Pathway Mediates the Activation of Cardiac Macroautophagy by Proteasomal Malfunction

Abstract: Rationale: The ubiquitin-proteasome system (UPS) and the autophagic-lysosomal pathway (ALP) are pivotal to proteostasis. Targeting these pathways is emerging as an attractive strategy for treating cancer. However, a significant proportion of patients who receive a proteasome inhibitor-containing regime show cardiotoxicity. Moreover, UPS and ALP defects are implicated in cardiac pathogenesis. Hence, a better understanding of the cross-talk between the two catabolic pathways will help advance cardiac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 60 publications
(85 reference statements)
3
53
0
Order By: Relevance
“…As reported, TFEB is dephosphorylated by calcineurin. During starvation and physical exercise, calcineurin induction triggers the TFEB nuclear translocation synergistically with mTORC1 inhibition ( Medina et al, 2015 ; Di Paola and Medina, 2019a ; Pan et al, 2020 ).…”
Section: The Specific Mechanism For Tfeb Activationmentioning
confidence: 99%
“…As reported, TFEB is dephosphorylated by calcineurin. During starvation and physical exercise, calcineurin induction triggers the TFEB nuclear translocation synergistically with mTORC1 inhibition ( Medina et al, 2015 ; Di Paola and Medina, 2019a ; Pan et al, 2020 ).…”
Section: The Specific Mechanism For Tfeb Activationmentioning
confidence: 99%
“…Recent studies have revealed that KSR1 could be ubiquitinated by E3 ligase praja2 [ 22 ]. Ubiquitin-proteasome system plays a key role in regulating intracellular signal pathways by regulating the expression, activity and localization of many endogenous proteins [ 31 ]. Ubiquitin can bind to the targeted protein through three enzymes E1, E2 and E3.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from substantia nigra tissues of rats by using TRIzol reagent, and RT-qPCR was performed as previously described [ 46 ]. Total RNA was quantified using the Nanodrop-2000 (Thermo Fisher Scientific) and reverse transcribed into complementary DNA (cDNA) using a PrimeScript RT Reagent kit.…”
Section: Methodsmentioning
confidence: 99%